2012 6th IEEE International Conference on Digital Ecosystems and Technologies (DEST) 2012
DOI: 10.1109/dest.2012.6227932
|View full text |Cite
|
Sign up to set email alerts
|

Linked data for humanities research — The SPQR experiment

Abstract: Abstract-Ancient texts represent a primary source for research in the classics. A substantial body of digital material has evolved enriching these texts. Unfortunately these data are often distributed across myriad locations, stored in diverse and incompatible formats and are either not available online or are made available only in isolation. This paper describes an investigation into using linked data principles and technologies to build bridges between these islands of data to deliver an integrated data lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Classics studies are akin to History in relying heavily on documents (ancient ones in fact) and so might be deemed quite similar to our latest case. The SPQR ('Supporting Productive Queries") project (Blanke et al, 2012) was retained nonetheless as highly relevant to our study, as it presents itself as "Linked data for humanities research".…”
Section: Case #4: Classicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classics studies are akin to History in relying heavily on documents (ancient ones in fact) and so might be deemed quite similar to our latest case. The SPQR ('Supporting Productive Queries") project (Blanke et al, 2012) was retained nonetheless as highly relevant to our study, as it presents itself as "Linked data for humanities research".…”
Section: Case #4: Classicsmentioning
confidence: 99%
“…In the field of Classics research, ancient texts are an important source of information. Even though a large amount of digital material has been created, it can be difficult to access due to its being distributed across locations, stored in diverse and incompatible formats, and either not available online or made available only in isolation (Blanke et al, 2012). The SPQR project uses LD principles and technology to link the existing datasets, "to deliver an integrated data landscape through which researchers can explore and so seek to understand this data" (Blanke et al, 2012, p. 1).…”
Section: Case #4: Classicsmentioning
confidence: 99%
“…gov/ndnp/. 2 See Barbera, 2013;Bizer et al, 2009;Blanke et al, 2012;Meroño-Peñuela et al, 2012;Rademaker et al, 2015;Sztyler et al, 2014. 3 For Canada see http://open.canada.ca/en/open-data and for the United Kingdom, https:// data.gov.uk/.…”
Section: Endnotesmentioning
confidence: 99%
“… 2 See Barbera, 2013; Bizer et al, 2009; Blanke et al, 2012; Meroño-Peñuela et al, 2012; Rademaker et al, 2015; Sztyler et al, 2014. …”
Section: Endnotesmentioning
confidence: 99%
“…In another experiment at King's College London, evaluation by researchers found that graph databases were taken up keenly by researchers in classics, as key concepts and documents of the classical world (in this case) could be browsed easily and contextualised with other related concepts. 30 For instance, a researcher might have been recording ancient inscriptions on-site and wish to research or contextualize particular words in them. They might wish to identify inscriptions, which refer to a particular person (e.g.…”
Section: Towards a New Kind Of Infrastructure: The Archive Graphmentioning
confidence: 99%